Critical success factors and challenges of women entrepreneurs in Klang Valley, Malaysia - Abdul, Mohani; Gunasagaran, Krishneswary; Kamarudin, Nurul Ain; Rahman, Mohammad Mizanur; Uddin, Mohammad Jamal; Rahman, Mohammad Sahabuddin (Penerbit Akademia Baru, 2017)
This paper explores critical success factors and challenges of women entrepreneurs in Klang Valley, Malaysia. Data was collected through a self-administered questionnaire which was distributed to 100 women entrepreneurs by using snowball sampling. The study revealed that 85% of these women had been exposed to entrepreneurship course before venturing into their business and 85% of them also have at least one family member involved in business. Attitude, skills, business strategy and environmental factors gave significant results; while the use of IT was insignificant. In terms of ranking, based on Pearson correlation coefficient, skills are ranked highest while business strategy, environment, attitude and use of IT are ranked as second, third, fourth and fifth respectively. The study also exhibited some problems faced by these women entrepreneurs before and during their business operation. The results of this study will be helpful to the entrusted government agencies in providing proper training or guidance in helping Malaysian women entrepreneurs.